Mapping damage and preservation of historical newspapers at the National Library of Indonesia - Khadijah, Ute Lies Siti; Winoto, Yunus; Sujana, Lusi Romaddyniah; Nursari, Tita; Septian, Falih Ijlal; Syahrul, Syahrul; Khatimah, Khusnul; Shuhidan, Shamila Muhammad (Universitas Padjadjaran, 2025)
Background: Historical newspapers serve as crucial primary sources, preserving a Indonesian nation's collective memory. However, their fragile material composition presents persistent preservation challenges for memory institutions, creating a need to assess the gap between collection conditions and existing safeguards. Purpose: This study aimed to systematically map the extent of physical deterioration in historical newspaper collections and assess the effectiveness of preservation measures implemented by the National Library of Indonesia (Perpusnas RI). Methods: The research used a quantitative descriptive design combined with the Analytical Hierarchy Process (AHP). A proportional sample of 400 bundles was drawn from a total of 25,814 bundles, representing four major historical periods of Indonesia. Results: Findings indicated that a majority of the collections exhibited moderate to severe damage, including high acidity (95%), foxing (90%), and fungal stains (65%). Crucially, only 5.25% of bundles had undergone physical conservation and 36.25% had been digitized, identifying torn paper and missing sections as the most critical categories requiring immediate intervention. Conclusion: The study concludes that systematic digitization serves as a sustainable preservation surrogate. There is an urgent need to address the significant preservation gap to ensure the long-term survival of Indonesia's documentary heritage. Implications: The findings imply a necessity for strengthening institutional policies, technical protocols, and human resource capacity. Theoretically, it establishes an evidence-based framework for newspaper preservation, while practically, it advocates for prioritizing AHP-based decision-making in conservation resource allocation.